A MORPHOLOGICAL ANALYSIS ON AFFIXES IN TOMBULU LANGUAGE - Senduk, Randy Kristoforus; Olii, Sanerita T.; Kamagi, Sarah (Journal of English Culture, Language, Literature and Education, 2021)
This study aimed to reveal affixes form and meaning in Tombulu language tenses especially on past present and future tenses Descriptive qualitative method used with applying Arikunto s procedure of collecting data which were interview and documentation While in analyzing data used Miles amp; Huberman which consisted of data reduction data display and conclusion drawing This study showed that there were different functions of Affixes in the tenses of Tombulu language and English The simple past tense was Infix im < em>< strong> and in < em>< strong> which were placed after vocal or consonant phonemes Simple present tense with Prefix mah < em>< strong> which was located to the beginning of the word Simple future tense with Infix um < em>< strong> which was placed after vocal or consonant phonemes Especially for the Infix um < em>< strong> and im < em>< strong> if it was combined with a root word that begins with the consonant phonemes p < em> and w < em> then there was a change where the Infix um < em>< strong> u m< em> and the infix im < em>< strong> nim< em> Affixes in Tombulu language tenses had different functions of affixes in English < p>